(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2009)
Social Responsibility is configured as a form of action by the organizations according to their role in society, not only try to generate more profits to shareholders but includes a number of elements to generate wellbeing for those involved in the workplace environment, social investment, market responsible, values and ethics. These practices differ and extrapolated to the companies that performed in turn becoming more sustainable and competitive advantage. This research aims to define those elements of Corporate Social Responsibility in the CA group of companies RENUTRE with the aim of design guidelines that reinforce the same as a competitive strategy. The research responds to a non-experimental design, reflecting the characteristics of the variables without any manipulation. It’s kind of field according to the actual facts, with a descriptive level to identify and analyze the behavior of the variables using their indicators. Some findings indicate that the analyzed elements have been implemented, however it is appreciated that this issue has not yet been internalized in general, considering daily activities and strategies are not sustainable and healthy business competition.